Density functional theory investigation of Bi(Ga,Al)O3solid solution for high-performance lead-free piezoelectric materials - Sittichain Pramchu (2018)
In this work, we have investigated the ferroelectric property of BiAlxGa(1-x)O3with x = 0.00, 0.25, 0.50, 0.75, and 1.00 for replacement of the widely use, PZT which is toxic. The techniques used are density functional theory with local density approximation (LDA) as well as projector augmented-wave method (PAW). The composition (x) was varied via setting the appropriated supercell. The solid solutions in both tetragonal (P4 mm) and rhombohedral (R3c) phase have been simulated to determine crystal stability, phase transition, and ferroelectric properties. From the results, the expected morphotropic phase boundaries (MPB) have not been observed because all R3c structures are more energetically stable than those of P4 mm. Therefore, Bi(Ga,Al)O3solid solution cannot display higher ferroelectricity than that of pure BiGaO3. However, the calculated polarization of Bi(Ga,Al)O3are still very high compared to other ferroelectric materials, e.g. AgNbO3and BaTiO3. This suggests that the considered solid solution could be one of lead-free candidates for future industrial applications. © 2013 Copyright Taylor and Francis Group, LLC.